A Study of Malaria - Related Pediatric Morbidity and Mortality in Ahmedabad, Gujarat State, India - N J Talsania; SN Vani (Medsci Publications, 2010)
Background: Malaria is one of the foremost public health problems in India. Aims:  To assess the syndromic diagnosis of fever in pediatrics patients. Method: The longitudinal hospital - based study was conducted in Pediatric ward of New Civil Hospital, Ahmedabad .Information was collected on a pretested semi structured schedule. After collection, the whole data was compiled; analyzed and appropriate statistical tests like simple proportions and chi-square (x2) test were applied. Result: A total of 4,515 children were admitted to the three Paediatric wards in New Civil Hospital from August 2009 to July 2010, of whom 584 (12.94 %) had three clinical symptoms. males were 2.5 times more brought than females, but the malaria rate was almost same in both sexes. Of the 584 clinical malaria admission, 15 died (C.F.R.: 2.6 %). The case fatality rate of males 9 (3 %) did not differ significantly from that of females (2.11 %). Conclusion the children presenting with a sequence of the symptoms of malaria, have been given radical treatment at home, 84-100% would have been correctly treated, 0-16% may have been false positive and unnecessarily treated.